2018
DOI: 10.11144/javeriana.upsy17-4.usdt
|View full text |Cite
|
Sign up to set email alerts
|

Using the Semantic Differential Technique to Assess Stereotypes toward Individuals with Disabilities: The Relevance of Warmth and Competence

Abstract: This study analyzes social perceptions towards groups with different types of disability, as well as the relationship between the judgments towards these groups, oneself and other significant individuals. The assessment was carried out using a Semantic Differential scale completed by181 participants. Results supported the Stereotype Content Model, as the different groups with disabilities were perceived in a more uniform way than those who did not share this label, and people with intellectual disability elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
6
1
1
Order By: Relevance
“…These obstacles affect the success of the socialization of persons with disabilities (Bell & Klein, 2001). Research on disability found a different treatment of persons with disabilities in the workplace (Bailey, 1991;Bell & Klein, 2001;Jenaro et al, 2018;Ren et al, 2008a). Different treatments in the work environment can be beneficial or negative for persons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These obstacles affect the success of the socialization of persons with disabilities (Bell & Klein, 2001). Research on disability found a different treatment of persons with disabilities in the workplace (Bailey, 1991;Bell & Klein, 2001;Jenaro et al, 2018;Ren et al, 2008a). Different treatments in the work environment can be beneficial or negative for persons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…People with disabilities often experience discrimination. There are stereotypes, stigma, negative bias, anxiety, and hatred (Colella, 1994;Colella & Stone, 2004;Desombre et al, 2018;Jenaro et al, 2018;Trani et al, 2016). Persons with disabilities are considered a burden that must be borne, and they must receive assistance in the work environment (Please et al, 2017;Foster, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the label “gamer” has emerged as both a symbol of pride for many game players as well as a negative, exclusionary stereotype. A stereotype is generally considered to be an overgeneralization of a concept, individual, or group which includes cognitive, emotional, and evaluative components (Bąk, 2001; Jenaro, Flores, & López-Lucas, 2018). Stereotypes are important as they contribute to the formation of attitudes toward others.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotypes are important as they contribute to the formation of attitudes toward others. This includes assigning characteristics to others, forming expectations of their behaviors, and feeling emotions toward them (Jenaro et al, 2018). The traditional gamer stereotype has many characteristic traits, including but not limited to age (adolescent), race (white), gender identity (cisgendered and male), sexual orientation (heterosexual), social aptitude (socially awkward and isolated), physical traits (overweight and unattractive), achievement (professionally unsuccessful or idle), and/or motivation (unmotivated) (Deshbandhu, 2016; Evans & Janish, 2015; Kowert et al, 2014; Shaw, 2012; Stone, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…De acuerdo con esto, se evidenció que estas categorías son producto del contexto en el que se construyen estas representaciones sociales dentro de la comunidad, en donde dicha condición se constituye como un rasgo permanente y transversal de los diferentes ámbitos de vida del sujeto que presenta algún tipo de discapacidad. Esto les acarrean valoraciones positivas y/o negativas, sin importar si estos miembros de la comunidad universitaria hayan tenido contacto o no con este sujeto (Collazos-Aldana, 2012;Jenaro et al, 2018). Inclusive, desde la postura de Collazos-Aldana (2012), la comunidad es propensa a resaltar esta condición más que las capacidades y habilidades de estos individuos, en otras palabras, se habla más de la limitación o de la dificultad que de la persona con discapacidad.…”
unclassified